Photocurrent characteristics of metal–AlGaN/GaN Schottky-on-heterojunction diodes induced by GaN interband excitation. (9th April 2018) - Tang, Xi; Li, Baikui; Chen, Kevin J.; Wang, Jiannong
Abstract: The photocurrent characteristics of metal–AlGaN/GaN Schottky-on-heterojunction diodes were investigated. When the photon energy of incident light was larger than the bandgap of GaN but smaller than that of AlGaN, the alternating-current (ac) photocurrent measured using lock-in techniques increased with the chopper frequency. Analyzing the generation and flow processes of photocarriers revealed that the photocurrent induced by GaN interband excitation featured a transient behavior, and its direction reversed when the light excitation was removed. The abnormal dependence of the measured ac photocurrent magnitude on the chopper frequency was explained considering the detection principles of a lock-in amplifier.